Breast cancer screening program in Lithuania: trends in breast cancer mortality before and during the introduction of the mammography screening programme - Steponavičienė, Laura; Briedienė, Rūta; Vansevičiūtė-Petkevičienė, Rasa; Gudavičienė, Daiva; Vincerževskienė, Ieva (Acta medica Lituanica, 2020)
BackgroundBreast cancer is the most frequent oncological disease as well as the leading cause of cancer death among women worldwide. Decline in mortality in economically strong countries is observed. This decline is mostly related to early diagnosis (improvement in breast cancer awareness and mammography screening program (MSP)) and more effective treatment. In the end of 2005, the MSP started in Lithuania. The main aim of this article was to evaluate breast cancer mortality during 22 years in Lithuania, as well as changes before the start of the MSP and during its implementation, in order to assess the influence of the MSP on mortality.Materials and MethodsAnalysis was based on data from the population-based Lithuanian Cancer Registry. Analysis of changes in mortality included the period from 1998 to 2019. Age standardized mortality rates were calculated for assessment of changes. Join-point regression analysis was used.ResultsApplying the segmental regression model, it was found that during the study period mortality was statistically significantly decreasing by -1.1% each year.  Mortality among women under the age of 50 decreased both before and during the implementation of MSP. Mortality in the target population also was already decreasing until the implementation of the program, but since 2006 significant reduction in mortality was observed in this group.ConclusionsOverall breast cancer mortality is decreasing in Lithuania. After the implementation of MSP the largest reduction in mortality was observed among the target population, however, it is not as pronounced as it could be with the well-organized MSP.
Keywords: breast cancer; mortality; trends; mammography screening program